Implementing the Independent Curriculum in Faith-Based Primary Education: A Case Study of Insan Mandiri Integrated Islamic School - Supadi, Supadi; Hartania, Intan Melya; Santosa, Heru; Musringudin, Musringudin (Journal of Nonformal Education, 2025)
Background - The implementation of the Independent Curriculum at the elementary school level has become a crucial issue in promoting adaptive, student-centered education. Research Urgency - Despite its nationwide rollout, the implementation of the Independent Curriculum in faith-based elementary schools remains underexplored, particularly in balancing national standards with religious and contextual values. This study is crucial to uncover how such schools adapt the curriculum in practice, providing insights for more inclusive and responsive education policies. Research Objectives - This study aims to describe the planning, implementation, and evaluation processes of the Independent Curriculum at SDIT Insan Mandiri, South Jakarta, while identifying its effectiveness and the challenges encountered. Research Method - Employing a descriptive qualitative approach, data was collected through observation, interviews, and document analysis. Research Findings - The findings reveal that learning plans are tailored to students’ potential and needs through the development of contextual teaching modules, including outdoor learning and the use of various media. Curriculum implementation involves innovative activities such as market days and infak collection, which contribute to students’ character development and social competence. Evaluation is conducted through Learning Communities and student self-reflection using color-coded cards as indicators of engagement and understanding. Research Conclusion - The study concludes that curriculum implementation aligns with differential, constructivist, and competency-based educational principles, despite technical constraints such as inconsistencies between textbooks and learning objectives and limited time for additional mentoring. Research Novelty/ Contibution - The novelty of this study lies in its participatory evaluation practices based on student self-reflection and collaborative learning communities, which remain underexplored in other elementary-level applications of the Independent Curriculum.